Preceptors' experiences of using structured learning activities as part of the peer learning model: A qualitative study. (January 2020) - Stenberg, Marie; Bengtsson, Mariette; Mangrio, Elisabeth; Carlson, Elisabeth
Abstract: The clinical environment is a vital component of nurse education, constantly changing due to constraints of the current health care systems such as increasing number of students and a limited number of preceptors. Peer learning, is gaining momentum as an educational model highly suitable for clinical placements. The peer learning model incorporates structured learning activities that support student activity, but little is reported of the actual structure and content of those activities. Thereby, the aim of this study was to explore precepting nurses' experience of using structured learning activities as part of the peer learning model during clinical placement. We used a qualitative research approach, using two open self-administered global questions. The result is based on the analysis of the written responses from 62 preceptors. Four categories followed the analysis: An opportunity for collaboration, An occasion for reflection, A new educational structure, and Recommendations for development. The preceptors perceived the structured learning activities as beneficial for increased collaboration and reflection among students. Moreover, utilizing the structured learning activities was perceived to be time saving for the preceptors, however this is an area where further research is needed. Highlights: Structured learning activities as part of peer learning seem to be timesaving. Structured learning activities allow for increased collaboration for nursing students. Structured learning activities allow for an observational role for the preceptor. Structured learning activities clearly aligned theory and practice.